Markers of inflammation and CD8+ T-cell activation, but not monocyte activation are associated with subclinical carotid artery disease in HIV - Longenecker, Chris T. (2013)
OBJECTIVE: To explore the relationships between lymphocyte and monocyte activation, inflammation, and subclinical vascular disease among HIV-1 infected patients on antiretroviral therapy. METHODS: Baseline mean common carotid artery (CCA) intima-media thickness (IMT) and carotid plaque (IMT >1.5cm) were evaluated in the first 60 subjects enrolled in the Stopping Atherosclerosis and Treating Unhealthy bone with RosuvastatiN in HIV (SATURN-HIV) trial. All subjects were adults, on stable ART with evidence of heightened T-cell activation (CD8+CD38+HLA-DR+ ≥19%) or increased inflammation (high sensitivity C-reactive protein ≥2mg/L). All had fasting LDL-cholesterol ≤130mg/dL. RESULTS: 78% were men and 65% African-American. Median (IQR) age and CD4+ count were 47(43,52) years and 648(511, 857) cells/µL, respectively. All had HIV-1 RNA<400 cps/mL. Mean CCA-IMT was correlated with log-transformed CD8+CD38+HLA-DR+% (r=0.326, p=0.043), interleukin-6 (r=0.283, p=0.028), soluble vascular cell adhesion molecule (sVCAM, r=0.434, p=0.004), tumor necrosis factor-α receptor-I (TNFR-I, r=0.591, p=<0.0001) and fibrinogen (r=0.257, p=0.047). After adjustment for traditional CVD risk factors, the association with TNFR-I (p=0.007) and fibrinogen (p=0.033) remained significant. Subjects with plaque (n=22, 37%) were older [51(7.7) vs. 43(9.4) years, mean(SD), p=0.002], had higher CD8+CD38+HLA-DR+% [31(24, 41) vs. 23(20,29)%, median(IQR), p=0.046] and higher sVCAM [737(159) vs. 592(160) ng/mL, p=0.008] compared to those without plaque. Pro-inflammatory monocyte subsets and serum markers of monocyte activation (soluble CD163 and soluble CD14) were not associated with CCA-IMT or plaque. CONCLUSIONS: Participants in SATURN-HIV have a high level of inflammation and immune activation that is associated with subclinical vascular disease despite low serum LDL-C.